Study on Fresh and Mechanical Properties of Polyblend Self-Compacting Concrete with Metakaolin, Lightweight Expanded Clay Aggregate, and SAP as Alternative Resources - S. S. Vivek; B. Karthikeyan; G. Ragul Kanna; Senthil Kumaran Selvaraj; Jose S; Ponnusamy Palanisamy; Tezeta Moges Adane (Advances in Civil Engineering)
This paper discusses the possibility of developing a lightweight self-compacting concrete (SCC) with self-curing capabilities. In this regard, a supplementary cementitious material metakaolin, a presoaked lightweight expanded clay aggregate (LECA), and a chemical agent, superabsorbent polymer (SAP), were incorporated in developing a self-compacting self-curing concrete possessing a target strength of 60 MPa through experimental investigations, and the results are reported. The research includes an analysis of basic material properties of constituent materials including fresh properties of concrete and mechanical properties such as compressive and splitting tensile strength. It was inferred from the experimental results that utilization of self-curing agents in SCC has enhanced the mechanical properties when compared with conventional SCC mix. In particular, a combination of 0.3% SAP and 15% LECA gave the optimum strength values. The optimum usage limit of both the materials is presented in this study, and the results prove that SCC can be used as an alternate resource without disturbing the natural resources.